The Long Pentraxin PTX3 in Bone Homeostasis and Pathology - Parente, Raffaella; Sobacchi, Cristina; Bottazzi, Barbara; Mantovani, Alberto; Grčevic, Danka; Inforzato, Antonio (Frontiers in Immunology, 2019)
The innate immune system is equipped with a number of germ-line encoded soluble pattern recognition molecules (PRMs) that collectively mediate the humoral host response to infection and damage in cooperation with cells and tissues of the immune and non-immune compartments. Despite the impressive diversity in structure, source and regulation across PRMs, these all share remarkably similar functions inasmuch as they recognize microbes and damaged tissues, activate complement, exert opsono-phagocytic activities, and regulate inflammation. The long pentraxin 3 (PTX3) is a prototypic soluble PRM. Long known as a major player in innate immunity, inflammation and matrix remodeling, only recently has PTX3 emerged as a mediator of bone homeostasis in rodents and humans. Ptx3-targeted mice exhibit reduced trabecular volume during bone development, and impaired callus mineralization following experimental fracture. The murine gene is expressed in vivo by non-hematopoietic periosteal cells in the early phases of fracture healing, and in vitro by maturing osteoblasts. Human osteoblasts do express the PTX3 protein, whose levels positively correlate with bone density in vivo and osteoblast proliferation and maturation in vitro, thus pointing to a role in bone deposition. Contrasting evidence, however, suggest osteoclastogenesis-promoting effects of PTX3, where its expression has been associated with periodontitis, arthritis, and bone metastasis, conditions hallmarked by inflammation and bone resorption. Here, we review past and recent literature on the functions exerted by this long pentraxin in bone biology, with major emphasis on physiological skeletal remodeling, fracture healing, and chronic diseases of the bone.